2018
DOI: 10.1097/cad.0000000000000664
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoprogression with subsequent complete response and severe thrombocytopenia to checkpoint inhibitor immunotherapy in a patient with advanced mucosal melanoma of the sinonasal cavity

Abstract: In this case report, we describe a patient with an inoperable mucosal melanoma of the sinonasal cavity who achieved an ongoing complete response to combined immunotherapy with ipilimumab and nivolumab after initial pseudoprogression. Despite massive enlargement of the tumor 9 weeks after treatment initiation, we decided to continue with checkpoint inhibitor immunotherapy because of lacking potent therapeutic alternatives and the possibility of pseudoprogression. In the computed tomography scan 3 months later, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…We found 377 studies in the database search. After we deleted duplicates and we analyzed full texts, we included 14 case series and 66 individual case reports4,12–98 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…We found 377 studies in the database search. After we deleted duplicates and we analyzed full texts, we included 14 case series and 66 individual case reports4,12–98 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, response can be dissociated, as described by Chao et al, who reported on 4 patients with distant metastases at presentation treated with immunotherapy, out of which 2 had a response and 1 stability of the distant metastases but all had progression of disease at the primary site [159]. On the other hand, Philipp et al reported a case of initial pseudoprogression with subsequent complete response to combined ipilimumab and nivolumab in a patient affected by an inoperable sinonasal MM [160]. Intrinsic or acquired resistance to immunotherapy is poorly understood in MM but a recent publication reported 3 cases with switch of oncogenic driver (i.e., from KRAS, KIT, or no driver to NRAS) as the mechanisms determining acquisition of resistance to ICI [161].…”
Section: Mucosal Melanomamentioning
confidence: 98%
“…Although ICIs have been approved for treating various types of human malignancies, immune-related thrombocytopenia is most likely to be reported in NSCLC (5-11, 24, 25), melanoma (12)(13)(14)(15)(16)(17)(18)(19)(20), lymphoma (21), pancreatic cancer (22), and renal cell carcinoma (23), which is consistent with retrospective data from multiple institutions (26). Previous case and retrospective studies show that immune thrombocytopenia occurred in cancer patients treated with PD-1 inhibitor monotherapy, such as nivolumab or pembrolizumab, or a CTLA-4 inhibitor, or a combination with PD-1 and a CTLA-4 inhibitor ( Table 1).…”
Section: Incidence and Onset Of Immune Thrombocytopenia Induced By Icismentioning
confidence: 99%